Experimental investigation on the dynamic response of an innovative semi-submersible floating wind turbine with aquaculture cages. (November 2022) - Cao, Shugang; Cheng, Youliang; Duan, Jinlong; Fan, Xiaoxu
Abstract: Floating offshore wind turbines integrating with other functional devices can not only produce green electricity but also realize three-dimensional utilization of ocean space. Therefore, an innovative concept of semi-submersible floating wind turbine with aquaculture cages is proposed here. Correspondingly, its dynamical behaviors are required to be examined and investigated while various oceanic conditions are considered, including but not limited to an irregular wave condition and combined wind and wave conditions. Hence, a series of model tests in 1:40 scale is carried out in Shanghai Jiao Tong University Ocean Engineering Basin. Firstly, the scaling law and experimental setup are interpreted in detail. Calibrations of the wind generator and wave makers are carefully performed to ensure the accuracy and reliability of model tests. Then the dynamic responses of the new floating wind-aquaculture platform (FWAP) are studied experimentally, including the periods, damping, motions, accelerations and tower top loads. The results show that the existence of nets mainly has a damping effect on the dynamics of the new FWAP under different sea states. The motions, accelerations and tower top loads can be significantly increased when the FWAP undergoes 50-year extreme sea state. When the new FWAP is subjected to combined wind and wave, more complicated dynamic responses can be detected due to the rotation of wind turbine. The results can serve as a reference basis for the improvement of the new FWAP.